THE MEANING OF JOURNALIST INDEPENDENCE IN THE POST FILM (ROLAND BARTHES’ SEMIOTICS ANALYSIS) - Sari, Ika Rosdiana; Luthfie, Muhammad; Setiawan, Koesworo (Universitas Djuanda Bogor, 2019)
The Post film is based on a true story that tells the dilemmas of the Pentagon Papers publication involving Katharine Graham as the publisher of The Washington Post and her reporters. The Pentagon Papers is the United State Department of Defenseâ€™s research document that leaked by Daniel Ellsberg. This document revealed the government's lies about the Vietnam War. This study aims to analyze the meaning of journalist independence in The Post. Phenomenological qualitative research approach with descriptive method are used in this study. Data collection is done by observation and documentation study techniques. Roland Barthes' Semiotics theory, that divides the signification system into denotation, connotation, and myth, is used as the data analysis technique. The results shows that the Washington Post reporters are independence in publishing the Pentagon Papers. This is illustrated in Scene 113 that describes the meeting between Katharine Graham and her best friend, United States Secretary of Defense Robert McNamara, who responsible for the Pentagon Papers. The independence of journalist was shown by Katharine Graham, who tries not to be affected by McNamara who suggest her not to publish the document to the public.Â Keywords: Film, Independence of Journalist, Pentagon Papers, The Post